Vasculopathic changes, a somatostatin-producing neuroendocrine carcinoma and a jejunal gastrointestinal stromal tumor in a patient with type 1 neurofibromatosis. - Chetty, R; Vajpeyi, R (2009)
A 36-year-old male with neurofibromatosis type 1 (NF-1) presented with symptoms of obstructive jaundice. Imaging showed a periampullary mass, which on endoscopic retrograde cholangiopancreatography biopsy proved to be a somatostatinoma. A Whipple's procedure was performed and a somatostatinoma of the duodenum was confirmed. In addition, the patient had a gastrointestinal stromal tumor (GIST) of the jejunum with accompanying hyperplasia of interstitial cells of Cajal. The somatostatinoma was histologically characteristic with pseudoglandular and solid patterns together with psammoma bodies and lymphovascular invasion. The GIST did not display mutations in c-kit or platelet-derived growth factor receptor genes. The novel finding in this case was the presence of several vessels in the submucosa and muscularis propria of the duodenum displaying prominent intimal hyperplasia and in keeping with so-called neurofibromatosis-associated vasculopathy. These abnormal vessels were within and close to the somatostatinoma only and were not found away from the tumor. It is thought that the vasculopathy is related to NF-1 with abnormal neurofibromin possibly playing a role.